FACTORS OF ATTRACTIVENESS OF EDUCATION IN THE FIELD OF FINE AND DECORATIVE ARTS - Eivas, Larysa; Zenkovych, Yuliia; Kudrenko, Daria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article dwells upon the problem of revealing ways to increase the attractiveness of education in the field of fine and decorative arts for today’s youth. The specificity of "introducing" contemporary youth into the world of fine arts is studied, starting from the early stages (pre-school education) up to professional training. The factors affecting the decision of a person to choose a specialty in the field of art or education (artistic pedagogy) and the acquisition of corresponding professional qualifications are distinguished as follows: personal factor (abilities and talents of the individual), prestige as a motivational factor as well as information and organizational factors. The methodology of the study envisaged: systemic approach – in order to cover the problem consistently, systematically and holistically; an interdisciplinary approach to consider factors from the standpoint of pedagogy, psychology and sociology; historical approach – to estimate the state of formation of the system for future professional artist’s training as well as fine arts teacher’s training and decorative art tutor preparation. The scientific relevance of the research is the specification of the factors of attractiveness in terms of the choice of artistic or artistic-pedagogical specialty in the modern educational space. Generalization of the possibilities of vocational guidance of the educational system of teaching fine arts in its retrospective view (from the period of 1950-1991 to the beginning of the XXI century) is carried out. On the basis of the principal classification of the factors of choosing a profession and diagnosis results (questionnaires),certain recommendations are given in order to increase the attractiveness of education in the field of fine and decorative arts for both domestic and foreign students wishing to study in Ukraine.